Sex Differences in the Cancer Proteome - Chenghao Zhu; Nicole Zeltser; Jieun Oh; Constance H. Li; Paul C. Boutros (2025)
Proteins play a central role in cancer biology, as are the most common drug targets and biomarkers. Sex influences the proteome in many diseases, ranging from neurological to cardiovascular. In cancer, sex is associated with incidence, progression and therapeutic response, as well as characteristics of the tumour genome and transcriptome. The extent to which sex differences impact the cancer proteome remains largely unknown. To fill this gap, we quantified sex differences across 1,590 proteomes from eight cancer types, identifying 39 genes with sex-differential proteins abundance in adenocarcinomas of the lung and 15 genes in hepatocellular carcinomas, clear cell cancers of the kidney and adenocarcinomas of the pancreas. A subset of these protein differences could be rationalized by sex-differential copy number aberrations. Pathway analysis showed that sex-differential proteins in lung adenocarcinoma were enriched in MYC and E2F target pathways. These findings highlight the modest impact of sex on the cancer proteome, but the very limited power of existing proteomics cohorts for these analyses.